National Hispanic Democratic Caucus Fundraiser at Fresno Hilton Skyroom - Watkins, Howard::::::::: (1988)
Dan Ronquillo, Margaret Ronquillo, Attorney General John Van de Kamp, Nancy Cisneros, David Cisneros